Oxygen Nucleation of MoS2 Nanosheet Thin Film Supercapacitor Electrodes for Enhanced Electrochemical Energy Storage. Issue 14 (14th June 2021) - Nee Lou, Shi; Choon Heng See, Melvin; Lim, Sean; Sharma, Neeraj; Scott, Jason; Wang, Da‐Wei; Amal, Rose; Hau Ng, Yun
Abstract: A direct thin film approach to fabricate large‐surface MoS2 nanosheet thin film supercapacitors using the solution‐based diffusion of thiourea into an anodized MoO3 thin film was investigated. A dense MoS2 nanosheet thin film electrode (D‐MoS2 ) was obtained when the anodized MoO3 thin film was processed in a low thiourea solution concentration, whereas a highly porous MoS2 nanosheet thin film electrode (P‐MoS2 ) was formed at a higher thiourea solution concentration. The charge storage performances of the D‐MoS2 and P‐MoS2 thin films displayed an unusual increase in capacitance on extended cycling, leading to a capacitance as high as around 5–8 mF cm −2 . X‐ray diffraction and cross‐sectional microscopy revealed the capacitance enhancements of the MoS2 supercapacitors are attributable to the nucleation of a new MoS2‐ x O x phase upon cycling. For the D‐MoS2 nanosheet thin film, the formation and growth of the MoS2‐ x O x phase during cycling was accompanied by a volumetric expansion of the MoS2 layer. For the P‐MoS2 thin film, the nucleation and growth of the MoS2‐ x O x phase occurred in the pores of the MoS2 layer. The propagation of the MoS2‐ x O x phase also shifted the charge storage process in both films from a diffusion‐limited process to a capacitive‐dominant process. Abstract : To the core : An unusual nucleation and propagation of a MoS2‐ x O x structure enhances the capacitance of MoS2 electrodes prepared from combined anodization‐hydrothermal technique.